Сучасні українсько-польські стосунки: проблема історичної спадщини - Скрипчук, Любомир Іванович (ЧНУ, 2021)
This master's thesis is presented for defense in the specialty "International Relations" at the Yuri Fedkovych National University of Chernivtsi.
Keywords: Міжнародні відносини, українсько-польські стосунки, історична спадщина